Unveiling new insights: taming complex local fractional Burger equations with the local fractional Elzaki transform decomposition method - Alhamzi, Ghaliah; Prasad, J. G.; Alkahtani, B. S. T.; Dubey, R. S. (Frontiers in Applied Mathematics and Statistics, 2024)
This study aims to address the difficulties in solving coupled generalized non-linear Burger equations using local fractional calculus as a framework. The methodology used in this work, particularly in the area of local fractional calculus, combines the Elzaki transform with the Adomian decomposition method. This combination has proven to be a highly effective strategy for addressing non-linear partial differential equations within the local fractional context, which finds numerous practical applications. The proposed method offers a systematic and easily understandable procedure for tackling both linear and non-linear partial differential equations (PDEs). It provides an easy-to-follow path to solve these problems. We offer a real-world example that exhibits the method's successful use in resolving issues to corroborate its efficacy. The obtained solution is visually represented to illustrate the practical utility of this approach. 2010 Mathematics Subject Classification 34A34, 65M06, 26A33.